Prevalence and Antimicrobial Resistance Diversity of Salmonella Isolates in Jiaxing City, China - Ping Li; Li Zhan; Henghui Wang; Yong Yan; Miaomiao Jia; Lei Gao; Yangming Sun; Guoying Zhu; Zhongwen Chen (MDPI AG, 2024)
Nontyphoidal Salmonella (NTS) is a cause of foodborne diarrheal diseases worldwide. Important emerging NTS serotypes that have spread as multidrug-resistant high-risk clones include S. Typhimurium monophasic variant and S. Kentucky. In this study, we isolated Salmonella in 5019 stool samples collected from patients with clinical diarrhea and 484 food samples. Antibiotic susceptibility testing and whole-genome sequencing were performed on positive strains. The detection rates of Salmonella among patients with diarrhea and food samples were 4.0% (200/5019) and 3.1% (15/484), respectively. These 215 Salmonella isolates comprised five main serotypes, namely S. Typhimurium monophasic variant, S. Typhimurium, S. London, S. Enteritidis, and S. Rissen, and were mainly resistant to ampicillin, tetracycline, chloramphenicol, and trimethoprim/sulfamethoxazole. The MDR rates of five major serotypes were 77.4%, 56.0%, 66.7%, 53.3%, and 80.0%, respectively. The most commonly acquired extended-spectrum β-lactamase-encoding genes were blaTEM−1B, blaOXA-10, and blaCTX-M-65. The S. Typhimurium monophasic variant strains from Jiaxing City belonged to a unique clone with broad antibiotic resistance. S. Kentucky isolates showed the highest drug resistance, and all were MDR strains. The discovery of high antibiotic resistance rates in this common foodborne pathogen is a growing concern; therefore, ongoing surveillance is crucial to effectively monitor this pathogen.